SquiUa Protein: Chemical Composition and Nutritive Value - MATHEW, P T; NAIR, A LEKSHMY; PRABHU, P V (Fishery Technology, 2017)
Protein extract prepared from squilla (Grato squilla nepa), a commercially unexploited crustacean, was analysed for crude protein and essential amino acids.' All the essential amino acids except tryptophan and threonine were present in nutritionally adequate amounts. The protein was evaluated for its nutritional quality in respect of growth rate, protein efficiency ratio (PER) and liver nitrogen content by feeding on rats. Growth rates and protein efficiency ratios were similar in rats fed on casein, squilla protein and a combination of squilla protein and casein (1 :1) diet. The weight of liver and kidneys were normal